Burkholderia vaccines: are we moving forward? - Choh, Leang-Chung; Ong, Guang-Han; Vellasamy, Kumutha M.; Kalaiselvam, Kaveena; Kang, Wen-Tyng; Al-Maleki, Anis R.; Mariappan, Vanitha; Vadivelu, Jamuna (Frontiers in Cellular and Infection Microbiology, 2013)
The genus Burkholderia consists of diverse species which includes both ‘friends’ and ‘foes’. Some of the ‘friendly’ Burkholderia spp. are extensively used in the biotechnological and agricultural industry for bioremediation and biocontrol. However, several members of the genus including B. pseudomallei, B. mallei and B. cepacia, are known to cause fatal disease in both humans and animals. B. pseudomallei and B. mallei are the causative agents of melioidosis and glanders, respectively, while B. cepacia infection is lethal to cystic fibrosis patients. Due to the high rate of infectivity and intrinsic resistance to many commonly used antibiotics, together with high mortality rate, B. mallei and B. pseudomallei are considered to be potential biological warfare agents. Treatments of the infections caused by these bacteria are often unsuccessful with frequent relapse of the infection. Thus, we are at a crucial stage of the need for Burkholderia vaccines. Although the search for a prophylactic therapy candidate continues, to date development of vaccines has not advanced beyond research to human clinical trials. In this article, we review the current research on development of safe vaccines with high efficacy against B. pseudomallei, B. mallei and B. cepacia. It can be concluded that further research will enable elucidation of the potential benefits and risks of Burkholderia vaccines.